2019
DOI: 10.3389/fevo.2019.00078
|View full text |Cite
|
Sign up to set email alerts
|

Host Selection, Oviposition and Feeding by a Phytopathogen Vector, Diaphorina citri (Hemiptera: Liviidae), Modulated by Plant Exposure to Formic Acid

Abstract: Citrus volatiles and their breakdown products, such as formic and acetic acids, guide host finding by Asian citrus psyllids (Diaphorina citri). Formic acid elicits psyllid antennal responses and stimulates probing. This study investigated how exposure to vapor phase formic acid induced changes in plant volatile emissions, expression of plant defense genes, and modified psyllid host finding and feeding behaviors on susceptible and resistant citrus cultivars. Chemical analyses of headspace volatiles and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
1
7
1
Order By: Relevance
“…Overall, the waveforms produced by both D. citri nymphs and adults during the 18 h recording periods were generally similar to those reported previously for them on citrus [25,27]. Examples of typical EPG recordings for adult psyllids on each of the four plant species tested are provided in Figure 1.…”
Section: Electrical Penetration Graph Recordings Of D Citri Nymphs Asupporting
confidence: 78%
See 3 more Smart Citations
“…Overall, the waveforms produced by both D. citri nymphs and adults during the 18 h recording periods were generally similar to those reported previously for them on citrus [25,27]. Examples of typical EPG recordings for adult psyllids on each of the four plant species tested are provided in Figure 1.…”
Section: Electrical Penetration Graph Recordings Of D Citri Nymphs Asupporting
confidence: 78%
“…Phloem is more nutrient rich than xylem sap, and is important for nymphal development. Our previous studies showed that adults fed more extensively on xylem than phloem on citrus, compared to nymphs, to maintain water balance [24][25][26]. In the current study, the frequency of xylem feeding bouts on C. macrophylla was lower than that which occurred on weed species; this type of feeding was otherwise similar in duration per bout and total duration on both non-host weeds and citrus hosts.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Regarding the emitted light, Paris et al [19] observed that ACP adults were attracted to UV (390 nm), green (525 nm), and yellow (590 nm) light. Additionally, chemical volatile cues from Rutaceae are important for ACP hostplant location [20][21][22].…”
Section: Introductionmentioning
confidence: 99%